Introduction: Social Hour for Australia’s Scholars of Book History and Publishing Studies - Henningsgaard, Per (American Association of Australian Literary Studies, 2021)
Introduction to a special issue of Antipodes on the subject of book history and publishing studies in Australia and New Zealand.